ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA SMP DI KOTA BANDUNG PADA MATERI SPLDV - Amelia, Susan; Awwalin, Amsa Aulia; Hidayat, Wahyu (IKIP Siliwangi, 2021)
This study aims to determine how the students mathematical connection skills in the school solve SPLDV questions related to daily life. The method used in this research is qualitative descriptive. The subject in this study is class VIII SMP. The number of students used in this study amounted to 26 students. The data collection was in the form of an essay test instrument consisting of 3 items. Research data processing is done by measuring the percentage of each indicator in connection capability. The results if this study indicate that grade VIII students at the school have good mathematical connection skills in completing questions in the SPLDV material